2001
DOI: 10.1046/j.1462-5822.2001.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell contact-induced alterations in Salmonella enterica serovar Typhi lipopolysaccharide are critical for bacterial internalization

Abstract: SummaryThe invasion of Pseudomonas aeruginosa and Salmonella enterica serovar Typhi into epithelial cells depends on the cystic fibrosis transmembrane conductance regulator (CFTR) protein as an epithelial receptor. In the case of P. aeruginosa, the bacterial ligand for CFTR is the outer core oligosaccharide portion of the lipopolysaccharide (LPS). To determine whether serovar Typhi LPS is also a bacterial ligand mediating internalization, we used both P. aeruginosa and serovar Typhi LPS as a competitive inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…In summary, we have shown that the CFTR protein, which [15]) and the cellular localization of its host receptor (CFTR). A heat-and proteasesensitive factor produced by serovar Typhi is necessary for CFTR redistribution.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In summary, we have shown that the CFTR protein, which [15]) and the cellular localization of its host receptor (CFTR). A heat-and proteasesensitive factor produced by serovar Typhi is necessary for CFTR redistribution.…”
Section: Discussionmentioning
confidence: 89%
“…One mutant strain of serovar Typhi that produces truncated LPS core is not capable of binding the CFTR protein and has a greatly reduced ability to enter epithelial cells, while another isogenic mutant producing a slightly larger LPS core interacts with CFTR normally and has an invasive phenotype (15). We are currently analyzing these LPS mutants in an attempt to identify the precise region of the LPS that serves as the CFTR-binding ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that this interaction between WT-CFTR and P. aeruginosa leads to internalization of the bacterium by respiratory epithelial cells via lipid raft formation (25,56), induction of nuclear translocation of NF-B (42), activation of Src-like tyrosine kinases p59Fyn and p60Src followed by tyrosine phosphorylation of additional epithelial cell proteins (12), transcriptional activation of genes for interleukin-6 (IL-6), IL-8, CXCL1, and intercellular adhesion molecule 1 (40), and rapid apoptosis to resolve the infection (8). Multiple groups have additionally shown that binding of Salmonella enterica serovar Typhi pili and/or LPS to CFTR also mediates intestinal epithelial cell uptake of this organism (21,28,35,50). Overall, the lack of functional CFTR has been shown to affect a number of responses of the lung to P. aeruginosa, which appears to lead to a dampened early innate immune response allowing the organisms to eventually establish a chronic infection (34).…”
mentioning
confidence: 99%
“…Previous work (12,18) has demonstrated that the availability of CFTR on the epithelial plasma membrane correlates positively with serovar Typhi translocation to the gastric submucosa. This is likely due to the increased availability of epithelial CFTR for binding by its serovar Typhi-based ligand, lipopolysaccharide (13). Therefore, I determined whether commensal-stimulated redistribution of the CFTR receptor increased serovar Typhiepithelium adhesion.…”
mentioning
confidence: 99%